The Characteristics of Nutrient-Rich Instant Noodles Based on Mackerel (Scomberomorus commerson) and Mangrove Fruit Flour (Sonneratia Caseolaris): Karakteristik Mie Instan Kaya Nutrisi Berbahan Dasar Ikan Tenggiri (Scomberomorus Commerson) dan Tepung Buah Mangrove (Sonneratia Caseolaris) - Sumartini; Harepa, Nurul Syahida; Ratrinia, PW; Suryono, Muh; FS, Shiffa (Universitas Muhammadiyah Sidoarjo, 2022)
Instant noodles are a popular food and are often consumed by the community as a fulfillment of food needs in high activity, especially in the people of the capital city. The level of consumption of instant noodles always increases every year. Mangrove fruit with good nutritional content can potentially be used as mangrove fruit flour to be used as fortification of raw materials for making instant noodles. The advantage of mangrove fruit flour as an ingredient for instant noodles is that it is richer in nutrients. Whole wheat flour has a risk of gluten content in wheat flour, the impact can be detrimental to health. So it is necessary to have other alternatives that can reduce the use of wheat flour with risk. One of them is making noodles with various flour mixtures or with a mixture of fish meat to increase the protein value and essential fatty acids in it. One example of fish that is good for health is mackerel. The research method used was Completely Randomized Design (CRD) with 3 factors (F1, F2, F3, and control). Data analysis using SPSS 22 software with analysis of variance (ANOVA) 95% confidence level. Further tests were carried out using Duncan's test to determine the significant difference between each variable. The study showed that instant noodles could be produced from the formulation of wheat flour, mangrove fruit flour, and fish meal. There was an increase in the total ash total; crude fiber and crude protein content of instant noodles and there is an increase in the carbohydrate and fiber content of instant noodles, the use of mangrove fruit flour and mackerel fish meal has the potential to be a source of protein and fiber in the production of healthy instant noodles and is lower in gluten. The best results was obtained instant noodle formulation F2 (200 grams of wheat flour + 50 grams of mackerel fish meal + 50 grams of mangrove fruit flour). However, noodles produced from 100% wheat flour (control) were the most preferred instant noodles with a value of 4.75.